2008
DOI: 10.1016/j.pain.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of major depression, pain and somatic disorders on general functioning in the general adult population

Abstract: This study was carried out to assess the prevalence of major depressive disorder (MDD) in persons suffering from pain symptoms in various locations, both with and without comorbid somatic disorders and to analyze the single and combined effects of MDD, pain symptoms and somatic disorders on general functioning in the community. The 12-month prevalence of MDD, somatic disorders and pain symptoms, grouped according to location, were determined among 4181 participants from a community sample. Depression was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
2
20
1
Order By: Relevance
“…These body locations had already been mentioned by the authors of other studies on the relationship between pain and depression. That is the case for stomach or abdomen pains and for headaches (Baune et al, 2008;Means-Christensen et al, 2008). We could not confirm the significant correlation, however, between back or arm and leg pains and the development of depression in the following year, as found by other authors (Barkow et al, 2001(Barkow et al, , 2004Baune et al, 2008).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…These body locations had already been mentioned by the authors of other studies on the relationship between pain and depression. That is the case for stomach or abdomen pains and for headaches (Baune et al, 2008;Means-Christensen et al, 2008). We could not confirm the significant correlation, however, between back or arm and leg pains and the development of depression in the following year, as found by other authors (Barkow et al, 2001(Barkow et al, , 2004Baune et al, 2008).…”
Section: Discussioncontrasting
confidence: 53%
“…Along these lines, a study by Baune, Caniato, Garcia-Alcaraz, and Berger (2008) presented results showing that, regardless of the precise area of the body (head, neck, shoulders, chest, abdomen, back, arms, and legs), pain is related to a greater prevalence of depression. It is possible that any kind of pain may be associated with depressive symptoms and that its precise location is not a determinant factor in this relation.…”
mentioning
confidence: 99%
“…Bodily pain, for example, is considered an obstacle to one’s ability or motivation to engage in activities conducive to well-being (Gayman, Brown & Cui, 2011), and it is associated with depressive symptoms among people with functional limitations (Baune et al, 2008; Gayman et al, 2011). Additional tests (not presented) assessing the mediating role of bodily pain using a multiplicative pain inventory (Gayman et al, 2011) found no support for its inclusion as a mediator of the functional limitation severity—depressive symptoms relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Bodily pain, which varies considerably in its magnitude and chronicity, is described as a form of stressor exposure because it may present an obstacle to one's ability or motivation to engage in activities that are conducive to well-being (Gayman et al, 2011). Functional limitation and bodily pain are also both consistently linked with depressive symptoms (Baune et al, 2008;Breslin et al 2006;Brown & Turner, 2010;Gayman et al, 2011;Yang, 2006), which provides grounds for anticipating that they may be linked with alcohol use vis-à-vis its tension-reducing functions.…”
Section: Drinking As a Tension-reduction Strategymentioning
confidence: 99%